Employee Performance in Organization: Does It Bring Success? - Ian Nurpatria Suryawan; Klemens Wedanaji Prasastyo (Milestone: Journal of Strategic Management, 2026)
Employee performance is a critical factor in the hospitality industry, where service quality and operational efficiency strongly depend on employee behavior. However, various organizational and psychological factors may influence employee performance, including locus of control, organizational citizenship behavior (OCB), rewards, and work stress. This study aims to examine the influence of locus control, organizational citizenship behavior, and rewards on employee performance, with work stress acting as a mediating variable. Data was collected from 187 employees who had worked for at least two years, ranging from staff to managerial level, in one hotel in Tangerang and two hotels in Yogyakarta. The data were analyzed using path analysis to evaluate the direct and indirect relationships among variables. The results show that rewards have a significant positive effect on employee performance when mediated by work stress. Organizational citizenship behavior does not have a direct significant effect on employee performance; however, it shows a significant indirect effect through work stress. These findings indicate that employees’ voluntary work behaviors may influence performance when psychological pressure at work is considered. Furthermore, work stress has a significant negative effect on employee performance, indicating that higher stress levels can reduce employee effectiveness. This study contributes to the organizational behavior literature in the hospitality sector by highlighting the mediating role of work stress in explaining how organizational and psychological factors influence employee performance. The findings also provide practical implications for hotel management in designing reward systems and managing employee stress to improve performance.